RANCANG BANGUN MESIN PARUT KELAPA SKALA RUMAH TANGGA - Nata, Yudi; Aziz, Abdul; Nanjarullah, Adin; Gunawan, Egi; Yaman, Suaryo Abdul Nur; Juliana, Yoga (Universitas Nusa Putra, 2021)
To facilitate grating and maintain hygiene and increase grating capacity in households and small industries, tools or coconut grating machines have been made, many coconut grater machines are designed or made with various models and prices vary. One of the designs or designs circulating in the market is a grate engine that uses a motorized engine with gasoline fuel. This machine is designed in such a way as to increase safety for users, speed up the coconut grating process, increase capacity, and maintain the hygiene of grated coconut. However, coconut grating machine tools for household and small industries are still relatively expensive. In this design a tool is made with a redesign of the mini coconut grater machine to reduce material costs and manufacturing costs. Make changes to shape and dimensions for frames and supports. Besides that, there are also changes to engine components with household-scale electric motors with a power of 220 volts.